2017
DOI: 10.1371/journal.pone.0177408
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitylation of the acetyltransferase MOF in Drosophila melanogaster

Abstract: The nuclear acetyltransferase MOF (KAT8 in mammals) is a subunit of at least two multi-component complexes involved in transcription regulation. In the context of complexes of the ‘Non-Specific-Lethal’ (NSL) type it controls transcription initiation of many nuclear housekeeping genes and of mitochondrial genes. While this function is conserved in metazoans, MOF has an additional, specific function in Drosophila in the context of dosage compensation. As a subunit of the male-specific-lethal dosage compensation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…We therefore wondered if Hakai might regulate m 6 A levels by ubiquitination of MACOM components. To investigate this possibility we examined our previous ubiquitylome datasets from Drosophila S2 cells and found that Fl(2)d and Nito were among the ubiquitinated proteins 43 . Thus, we cloned both proteins in a GFP-tag containing vector and expressed them in control and Hakai depleted S2R+ cells to monitor their ubiquitination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore wondered if Hakai might regulate m 6 A levels by ubiquitination of MACOM components. To investigate this possibility we examined our previous ubiquitylome datasets from Drosophila S2 cells and found that Fl(2)d and Nito were among the ubiquitinated proteins 43 . Thus, we cloned both proteins in a GFP-tag containing vector and expressed them in control and Hakai depleted S2R+ cells to monitor their ubiquitination.…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitylome and proteome analysis of control and Hakai depleted SILAC S2R+ cells or Fl(2)d/Vir depleted S2R+ cells was performed as described previously 43 , 48 . Following modifications were made: S2R+ cells were grown in Schneider medium (Dundee Cell) supplemented with either heavy (Arg10, Lys8) or light amino acids (Arg0, Lys0) (Sigma) or without supplement for the label-free proteomes (Fl(2)d and Vir KD).…”
Section: Methodsmentioning
confidence: 99%
“…For immunofluorescence microscopy (IFM), 0.5 * 10 6 L2-4 cells after RNAi treatment in 200–500 μl growth medium were seeded into each well of a 3-well (14 mm) object slide (Thermo Fisher) and incubated for 2 h at 26°C. Immunofluorescence staining was performed as described in (40) with slight modifications. Briefly, cells were washed in phosphate-buffered saline (PBS), fixed for 7.5 min with 2% (v/v) formaldehyde (FA) in PBS on ice and permeabilized for 7.5 min with 1% (v/v) FA in PBS with 0.25% (v/v) Triton-X 100 on ice.…”
Section: Methodsmentioning
confidence: 99%
“…For immunofluorescence microscopy (IFM), 0.5 * 10 6 L2-4 cells after RNAi treatment in 200 -500 µL growth medium were seeded into each well of a 3-well (14 mm) object slide (Thermo Fisher) and incubated for 2 h at 26°C. Immunofluorescence staining was performed as described in (Schunter et al, 2017)…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%